2018
DOI: 10.3390/su10020385
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Risk of Walking Scenarios Based on Macroscopic Flow Model and Crowding Force Analysis

Abstract: Abstract:In recent years, accidents always happen in confined space such as metro stations because of congestion. Various researchers investigated the patterns of dense crowd behaviors in different scenarios via simulations or experiments and proposed methods for avoiding accidents. In this study, a classic continuum macroscopic model was applied to simulate the crowded pedestrian flow in typical scenarios such as at bottlenecks or with an obstacle. The Lax-Wendroff finite difference scheme and artificial visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…Wu et al [11] investigated the crowding forces in a metro system and found that the maximum forces during boarding, travelling, and alighting are 650 N, 133 N, and 89 N, respectively. Li et al [12] found the maximum crowding force in bottleneck situation is 90.2 N, and the relationship between crowding force and crowd density is an exponential function.…”
Section: B Crowding Forcementioning
confidence: 99%
See 4 more Smart Citations
“…Wu et al [11] investigated the crowding forces in a metro system and found that the maximum forces during boarding, travelling, and alighting are 650 N, 133 N, and 89 N, respectively. Li et al [12] found the maximum crowding force in bottleneck situation is 90.2 N, and the relationship between crowding force and crowd density is an exponential function.…”
Section: B Crowding Forcementioning
confidence: 99%
“…Simulation models of high density crowds [1], [4], [12], [16] include microscopic and macroscopic models. Microscopic models include discrete models, continuous models, and agent-based models (ABM) [17].…”
Section: Related Work a High Density Crowdmentioning
confidence: 99%
See 3 more Smart Citations